Prevalence and factors associated with intestinal parasitic infection among under-five children in and around Haro Dumal Town, Bale Zone, Ethiopia - Eshetu Gadisa; Kefiyalew Jote (BMC, 2019)
Abstract Background Intestinal parasitic infection is diversified illness and diseases caused millions morbidity among under-five children lives in developing countries particularly vulnerable rural communities. Deworming coverage in such community is low. The aim of this study was to determine the prevalence and associated risk factors of intestinal parasitic infections (IPIs) among under-five children live in and around Haro Dumal Town. Methods Community-based cross-sectional study was conducted in 561 randomly selected under-five children from June to August, 2018. The stool samples were collected and examined by basic parasitological techniques. Data related to socio-demographic and risk factors were collected using a self administered questionnaire. Statistical data analysis was done using SPSS version 21 and the bivariate and multivariate logistic regression used to compute the association between variables. P-value of < 0.05 was statistical significance. The results Of the 561 total under-five children, 216 (38.5%) were found to be infected with intestinal parasites. E.histolytica/dispar (15.3%) was the most prevalent parasite, followed by hook worm (14.4%) and T.trichuria (13.9%). Regarding risk factors, geo-phage [(AOR = 4.7; 95%CI: 2.0-10.4), P < 0.001], tungiasis [(AOR = 3.1; 95%CI: 1.1-6.6), P < 0.001], eating raw vegetable [(AOR = 1.3; 95%CI: 1.4-3.3), P < 0.001] were significantly associated with intestinal parasitic infections. Conclusion Intestinal parasitic infections (IPIs) were found to be highly prevalent in the study area. Hence, improving sanitation, controlling ecto-parasite such as tungiasis, provision of safe water and successful mass-deworming are important.